Grammatical, Morphological and Spelling solecisms in scientific writing in Sudan - Al - Bashir, ‏​‏​‏​​‏​‏​​‏​‏​‏​‏​‏​‏ Saadia Moussa Omar (Arab Journal for Sciences and Research Publishing, 2018)
This study aims at investigating the old and renewed phenomena of solecism, demonstrating its history and how it affects those who encounter it and their communities, then tracking its common manifestations in scientific writing, i. e. pure science topics written in Arabic language, in order to identify the problems encountered by researchers when trying to write in Arabic. This was done through collecting samples of these writings and analyzing them linguistically (in terms of grammar, morphology and spelling). I adopted descriptive methodology to demonstrate the phenomena and its contemporary manifestations, giving examples from some research and master degree dissertations written in Arabic language prior to being proofread. The study classified that set of vocabulary items and expressions according to mere linguistic criteria to find that they were grammatical, morphological and spelling solecisms. Then the paper established what went wrong, providing descriptions and explanations, then determining the proper use by establishing arguments for that through examples of accurate classical Arabic expressions taken as quotes from the Holy Quran, poems and views of the scholars. The study revealed a number of grammatical, morphological and spelling mistakes common among researchers. In the light of the findings: the study made some recommendations that would help researchers avoid such mistakes in the future.